Maternal serum alpha-fetoprotein and previous neural tube defects. - Wald, N; Barker, S; Peto, R; Brock, D; Bonnar, J (1976)
A case-control study involving 63 pregnancies showed that women who had previously had an infant with anencephaly or spina bifida did not have raised serum alpha-fetroprotein (AFP) levels in subsequent unaffected pregnancies. The value of a serum AFP determination in such women is discussed. If the serum AFP level is normal and if ultrasonography excludes anencephaly the risk of spina bifida might be low enough (about 1 per cent) to make diagnostic amniocentesis difficult to justify. Conversely, a high serum AFP value in such women should not be acted on without confirmation of an abnormality by ultrasonography and, if that is negative, by diagnostic amniocentesis.